The management of esophago-gastric necrosis due to caustics ingestion: Anastomotic reinforcement with Cyanoacrylate glue and damage control with Vacuum Assisted Closure Therapy—A case report. (2019) - Picciariello, A.; Papagni, V.; Martines, G.; Palasciano, N.; Altomare, D.F.
Highlights: Optimal timing to treat esophago-gastric necrosis due to caustic ingestion. Proposal of three steps approach to manage esophago-gastric necrosis. Use of Cyanoacrylate glue to reinforce anastomosis. Vacuum Assisted Closure for damage control after surgery. Abstract: Introduction: The surgical treatment of a complete gastric necrosis due to caustic ingestion is extremely challenging and life threatening. In this emergency scenario, a first-time reconstruction of the gastrointestinal tract is often dangerous for the patient because of the high risk of infections and anastomosis leakage. Literature lacks of clear indications for the management of this condition. Presentation of case: Male patient with history of major depression disorder was admitted to our Emergency Unit after the ingestion of muriatic acid. CT scan showed massive pneumo-peritoneum with esophago-gastric thickening. Free fluids in the abdominal cavity were detected. Intraoperative finding was a complete necrosis of the stomach and corrosion of the lower esophagus. Discussion: In this case report we proposed a first approach with the drainage and lavage of the abdomen cavity. Then, an esophago-jejunum anastomosis reinforced by Cyanoacrylate glue was performed and a damage control with VAC therapy (Vacuum Assisted Closure) was carried out. Conclusion: Cyanoacrylate glue could be considered useful and efficient in the reinforcement of anastomosis even in emergency surgical procedures. Damage control using VAC allows to keep a good control of the surgery performed.